GLOBAL REGION AS A UNIT OF WORLD POLITICAL SYSTEM OF THE XXI CENTURY - M. L. Lagutina (Сравнительная политика)
One of the major tendencies of today’s world development is a transformation of special coordinates of world politics, shifting geopolitics of the XXI century world system as a result of two processes: globalization and regionalization. This entails the consolidation of new centers of power including global regions which are transforming into key units of world politics of the XXI century.